2021
DOI: 10.1016/j.nlm.2021.107446
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal striatum and the temporal expectancy of an aversive event in Pavlovian odor fear learning

Abstract: Interval timing, the ability to encode and retrieve the memory of intervals from seconds to minutes, guides fundamental animal behaviors across the phylogenetic tree. In Pavlovian fear conditioning, an initially neutral stimulus (conditioned stimulus, CS) predicts the arrival of an aversive unconditioned stimulus (US, generally a mild foot-shock) at a fixed time interval. Although some studies showed that temporal relations between CS and US events are learned from the outset of conditioning, the question of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Later research suggested that DA release may be restricted to the shell as opposed to the core (Martinez et al, 2008;Pezze et al, 2001;. Yet, other in-vivo microdialysis studies found that during fear acquisition and recall, DA levels decreased in the whole striatum and dorsal striatum but did not change in the dorsolateral striatum (Boulanger-Bertolus et al, 2021;Katoh et al, 1996;Matsumoto et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later research suggested that DA release may be restricted to the shell as opposed to the core (Martinez et al, 2008;Pezze et al, 2001;. Yet, other in-vivo microdialysis studies found that during fear acquisition and recall, DA levels decreased in the whole striatum and dorsal striatum but did not change in the dorsolateral striatum (Boulanger-Bertolus et al, 2021;Katoh et al, 1996;Matsumoto et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…[Insert figure 1 1997; Lane et al, 1982;Morrow et al, 1995;Tsuchiya et al, 1996a) levels of DA and its metabolites (DOPAC or HVA) from ex-vivo whole striatum, dorsal striatum and nucleus accumbens. Most but not all in-vivo microdialysis studies reported DA release in the nucleus accumbens during fear acquisition, recall, and extinction acquisition (Boulanger-Bertolus et al, 2021;Fulford et al, 2007;Kawade et al, 2023;Wilkinson et al, 1998;Young et al, 1993;Young, 2004). Later research suggested that DA release may be restricted to the shell as opposed to the core (Martinez et al, 2008;Pezze et al, 2001;.…”
Section: Methodsmentioning
confidence: 99%
“…Most, but not all, rat studies using in vivo microdialysis reported DA release in the nucleus accumbens during fear acquisition, recall and extinction training (Boulanger-Bertolus et al, 2021;Fulford & Marsden, 2007;Kawade et al, 2022;Wilkinson et al, 1998;Young et al, 1993;Young, 2004), and this release may differ in the accumbal shell versus the core (Martinez et al, 2008;Pezze et al, 2001Pezze et al, , 2002. Yet, others have reported decreased or unaltered DA microdialysis measurements in the whole striatum and dorsal striatum (Boulanger-Bertolus et al, 2021;Katoh et al, 1996;Matsumoto et al, 2005) (Table S5).…”
Section: It Is Unclear How Striatal Da Levels or Terminals Respond Du...mentioning
confidence: 99%